2014
DOI: 10.1094/pdis-03-14-0303-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Fusarium oxysporum f. sp. lycopersici Race 3 and F. oxysporum f. sp. radicis-lycopersici in Tomatoes in the Azapa Valley of Chile

Abstract: Tomato (Solanum lycopersicum L.) is an important crop in the Azapa Valley (18°35′ S, 69°30′ W) in northern Chile, with approximately 600 ha of fresh tomatoes under greenhouses. Cultivars resistant to Fusarium oxysporum f. sp. lycopersici (FOL) races 1 and 2 are mainly used. However, in 2012 and 2013, Fusarium wilt incidence was 2 to 3%. Symptoms appeared unilaterally and consisted of yellowing, leaf wilting of lower leaves, dark brown vascular discoloration, and plant death. The aim of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, these primer pairs were also used in the identification of physiological races of F. oxysporum f. sp. lycopersici in Northeast Brazil and Chile (Barboza et al 2013;Sepúlvedachavera et al 2014). This experiment, through the molecular identification method, showed that in addition to race 1 and race 2, there is also race 3 in Shanxi, which is the first report of physiological race 3 causing tomato Fusarium wilt in China.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, these primer pairs were also used in the identification of physiological races of F. oxysporum f. sp. lycopersici in Northeast Brazil and Chile (Barboza et al 2013;Sepúlvedachavera et al 2014). This experiment, through the molecular identification method, showed that in addition to race 1 and race 2, there is also race 3 in Shanxi, which is the first report of physiological race 3 causing tomato Fusarium wilt in China.…”
Section: Discussionmentioning
confidence: 80%
“…Decades of research have revealed that crop succession can lead to soil-borne diseases such as Fusarium crown and root rot (FCRR), an emerging disease that seriously threatens tomato (Solanum lycopersicum L.) production in most countries (Polizzi et al, 2011;Cordero-Ramirez et al, 2013;Sepulveda-Chavera et al, 2014). FCRR can occur from the seedling stage to the fruiting stage in tomato plants.…”
Section: Introductionmentioning
confidence: 99%
“…radicis-lycopersici (Forl), with race 3 and Forl causing the greatest damage [ 16 ]. The majority of commercial hybrid tomato varieties have resistance to Fol 1 and 2, but not Fol 3 nor Forl , leaving plants without resistance to these two particular forms [ 17 ].…”
Section: Introductionmentioning
confidence: 99%